Memadukan Sejarah dan Pariwisata: Implementasi Kebijakan Urban Heritage Tourism Di Kampung Peneleh Surabaya: Combining History and Tourism: Implementation of Urban Heritage Tourism Policy in Kampung Peneleh Surabaya - Nurany, Fierda; Irianto, Heru; Prasetijowati, Tri; Ismail, Ismail; Yusufi, Arinda Devira; Bachtiar, Rizky Nur (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
Global tourism is now leading to authentic and cultural experiences, with urban heritage tourism as a growing trend. Surabaya, as a historic city, has great potential in history-based tourism, especially in Kampung Peneleh. This study analyzes the implementation of urban heritage tourism policies in Peneleh Village, focusing on the challenges and opportunities for its development. The method used is descriptive qualitative through in-depth interviews and document analysis. Results show four main challenges: (1) ineffective communication between governments, communities, and tourism actors, leading to program overlap and low community participation; (2) limited resources, especially funds, which hinder the provision of supporting facilities; (3) the attitude of the community is less proactive; and (4) a complicated and slow bureaucratic structure. This study concludes that increased coordination, resource support, and community participation are very important to optimize the potential of heritage tourism in Peneleh Village. It is recommended to improve communication mechanisms, find alternative funding, and reform bureaucracy for inclusive and sustainable tourism development